The influence of grouting and reinforcement ratio in the concrete block masonry compressive behavior - Camacho, J. S.; Logullo, B. G.; Parsekian, G. A.; Soudais, P. R. N. (IBRACON - Instituto Brasileiro do Concreto, 2015)
This paper presents an experimental investigation on the compressive strength and stress-strain curves of concrete block masonry with varying block and grout strengths and reinforcement ratio. The three-block prisms, built with 8.5 and 15.0 MPa blocks, were tested hollow and filled with 17.0 and 30.0 MPa compressive strength grouts. In addition, prisms and walls with reinforcement rates of 0.15%, 0.40% and 1.0 % were also tested. With the results, it was possible to measure the compressive strength and stress-strain behavior of masonry with inclusion of different grout and reinforcement components, giving parameters for better evaluation of their performance and design. Among the conclusions, it was observed that increasing the compressive strength of masonry is not proportional to the increase of the grouting area and the efficiency of reinforcement to increase compressive strength is low. Stress-strain curves for the several materials combinations are made available.

Este trabalho apresenta uma investigação experimental do comportamento estrutural, resistência à compressão axial e deformabilidade, da alvenaria de bloco de concreto em função da variação da resistência dos blocos e graute e da taxa de armadura. Os prismas de três fiadas de altura, construídos com blocos de 8,5 e 15,0 MPa, foram ensaiados ocos e preenchidos com grautes de 17,0 e 30,0 MPa. Além destes, também foram ensaiados prismas e paredes armadas com taxas de 0,15%, 0,40% e 1,0%. Com os resultados foi possível mensurar a variação da resistência e os diagramas tensão-deformação da alvenaria com a inserção destes componentes (graute e armadura), fornecendo parâmetros para melhor avaliação de seu desempenho para projeto. Entre as conclusões, pode-se afirmar que o aumento da resistência à compressão das alvenarias não é proporcional ao aumento de área pelo grauteamento e que é baixa a eficiência da presença de armaduras para aumento da resistência a compressão. São disponibilizados os diagramas tensão-deformação para as várias combinações de materiais.
Influência do graute e da taxa de armadura no comportamento à compressão da alvenaria de blocos de concreto
Keywords: concrete blocks; reinforcement; masonry; compressive strength; stress-strain curve; blocos de concreto; armadura; alvenaria estrutural; resistência a compressão; curva tensão-deformação